2020
DOI: 10.3390/rel11120682
|View full text |Cite
|
Sign up to set email alerts
|

Religious Values in Liberal Democracy

Abstract: Religious values neither wholly threaten nor wholly reinforce the stability of liberal democracy. This depends upon how they may be interpreted and applied. The recent influence of Christian nationalists, who would promote a specific interpretation of Christianity as the only legitimate basis for public policy, and of those who would elevate religious liberty above all other rights, does not promote pluralism. Although people should be able to live out their religious commitments, it is the state, not individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The religious value is inevitably essential to exist (Ariza et al, 2020;Astapov & Krasnova, 2022;Astavov & Krasnova, 2022;Gill, 2020;González-Gijón et al, 2019;Pusztai et al, 2021). It is in line with some crucial instructional objectives i.e.…”
Section: Introductionmentioning
confidence: 95%
“…The religious value is inevitably essential to exist (Ariza et al, 2020;Astapov & Krasnova, 2022;Astavov & Krasnova, 2022;Gill, 2020;González-Gijón et al, 2019;Pusztai et al, 2021). It is in line with some crucial instructional objectives i.e.…”
Section: Introductionmentioning
confidence: 95%
“…While these features may lead to higher-order interactions, no research has explored the extent to which this dialogic dynamic can foster intercultural dialogues that enhance the attractiveness of values such as love, kindness, humility, or generosity. Especially in times where freedom is jeopardized in many contexts (Gill 2020), this study opens up new horizons for intercultural dialogues that nurture fundamental human values, which might bring renewed hope for future generations.…”
Section: Introductionmentioning
confidence: 99%
“…However, research has widely demonstrated how actions grounded in values such as love, friendship, or solidarity have the potential to enhance social cohesion; to provide emotional, economic, or other kinds of support; and to promote health and the public good (Gill 2020;Leon-Jimenez 2020). At the individual level, neuroscience has also evidenced how kindness fosters a healthy brain (Galante et al 2014) and leads to relationships characterized by pleasure and desire (Racionero-Plaza et al 2020).…”
Section: Introductionmentioning
confidence: 99%